2022
DOI: 10.3205/dgkh000410
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention requirements for the medical care of immunosuppressed patients: recommendations of the Commission for Hospital Hygiene and Infection Prevention (KRINKO) at the Robert Koch Institute

Abstract: In Germany, guidelines for hygiene in hospitals are given in form of recommendations by the Commission for Hospital Hygiene and Infection Prevention (Kommission für Krankenhaushygiene und Infektionsprävention, “KRINKO”). The KRINKO and its voluntary work are legitimized by the mandate according to § 23 of the Infection Protection Act (Infektionsschutzgesetz, “IfSG”). The original German version of this document was published in February 2021 and has now been made available to the international profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 408 publications
0
2
0
Order By: Relevance
“…During their research over a period of 10 years, the researchers observed this phenomenon several times [26]. Hospital renovation/construction is considered to be a major source of invasive healthcare-associated fungal infections; thus, planning such activities requires the preparation of appropriate safeguards [5,15,21]. It can be emphasized that there is a need for monitoring airborne fungal spore concentrations and determining breakpoint values [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During their research over a period of 10 years, the researchers observed this phenomenon several times [26]. Hospital renovation/construction is considered to be a major source of invasive healthcare-associated fungal infections; thus, planning such activities requires the preparation of appropriate safeguards [5,15,21]. It can be emphasized that there is a need for monitoring airborne fungal spore concentrations and determining breakpoint values [27].…”
Section: Discussionmentioning
confidence: 99%
“…The risk can be reduced by the installation of air-conditioning systems with HEPA (high-efficiency particulate air) filters, a high frequency of air exchanges (at least 12 per hour) and appropriate differentiation of air pressure in individual rooms, limiting the influx of microorganisms from unprotected areas. The isolation rooms in such wards consist of a patient room with positive air pressure, a shower, a toilet, and an anteroom (with negative air pressure), which separates the patient room from the corridor (most often without a HEPA filter) [5,15]. The proper functioning of HEPA systems requires adequate technical supervision, including the replacement of filters, and should be supported with microbiological surveillance of the air quality [5].…”
Section: Introductionmentioning
confidence: 99%